Cultural Understanding of Wounds, Buruli Ulcers and Their Management at the Obom Sub-district of the Ga South Municipality of the Greater Accra Region of Ghana. - Eric Koka; Dorothy Yeboah-Manu; Daniel Okyere; Philip Baba Adongo; Collins K Ahorlu (Public Library of Science (PLoS), 2016)
This study was conducted with the aim to understand some of the cultural belief systems in the management of wounds and patients practices that could contaminate wounds at the Obom sub-district of the Ga South Municipality of Ghana.This was an ethnographic study using in-depth interviews, Focus Group Discussions and participant observation techniques for data collection. Observations were done on Buruli ulcer patients to document how they integrate local and modern wound management practices in the day-to-day handling of their wounds. Content analysis was done after the data were subjected to thematic coding and representative narratives selected for presentation.It was usually believed that wounds were caused by charms or spirits and, therefore, required the attention of a native healer. In instances where some patients' wounds were dressed in the hospital by clinicians whose condition/age/sex contradict the belief of the patient, the affected often redress the wounds later at home. Some of the materials often used for such wound dressing include urine and concoctions made of charcoal and gunpowder with the belief of driving out evil spirits from the wounds.Clinicians must therefore be aware of these cultural beliefs and take them into consideration when managing Buruli ulcer wounds to prevent redressing at home after clinical treatment. This may go a long way to reduce secondary infections that have been observed in Buruli ulcer wounds.